The Effectiveness of Behavioral Counseling with Modeling Techniques to Improve Student Self-Achievement - I Ketut Dharsana; Wayan Eka Paramartha (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study aims to determine the difference between before and after treatment and to determine the effect of behavioral counseling with modeling techniques to improve student self-achievement. The research was conducted at SMK Negeri 1 Singaraja in class X, and used a randomized controlled trial (RCT) research design. Sampling in this study through simple random sampling which took 2 research samples, namely the experimental and control classes. The results of this study indicate the influence of behavioral counseling with modeling techniques to increase self-achievement through the effect size test. Based on these results, the researcher recommends behavioral counseling with modeling techniques to increase self-achievement in school.